2009
DOI: 10.1088/1758-5082/1/1/015003
|View full text |Cite
|
Sign up to set email alerts
|

Precision extruding deposition (PED) fabrication of polycaprolactone (PCL) scaffolds for bone tissue engineering

Abstract: Bone tissue engineering is an emerging field providing viable substitutes for bone regeneration. Recent advances have allowed scientists and engineers to develop scaffolds for guided bone growth. However, success requires scaffolds to have specific macroscopic geometries and internal architectures conducive to biological and biophysical functions. Freeform fabrication provides an effective process tool to manufacture three-dimensional porous scaffolds with complex shapes and designed properties. A novel precis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
106
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(111 citation statements)
references
References 21 publications
1
106
0
1
Order By: Relevance
“…Wiria et al [23] reported on the in vitro cell ingrowth of PCL/HA scaffolds fabricated via SLS, however, even though the success of the addition of a bioactive phase is anticipated, the in vivo performance of such composite scaffolds has not been extensively reported. Reports on in vivo testing of PCL based scaffolds fabricated by other rapid prototyping techniques are limited to small animal models [30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Wiria et al [23] reported on the in vitro cell ingrowth of PCL/HA scaffolds fabricated via SLS, however, even though the success of the addition of a bioactive phase is anticipated, the in vivo performance of such composite scaffolds has not been extensively reported. Reports on in vivo testing of PCL based scaffolds fabricated by other rapid prototyping techniques are limited to small animal models [30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37] Among them, the microextrusion bioprinters controlled by the extrusion of a material robotically with a microextrusion nozzle has been widely used in 3D bioprinter development. The stage or microextrusion head moves along x and y axis, in this way a layer is deposited as a foundation for the next layer when the extrusion head rises along z axis.…”
mentioning
confidence: 99%
“…Nozzle-based printing can be categorized into two groups: techniques with melting process and techniques without melting process. Nozzle-based printing with melting process include fused deposition modelling (FDM), precise extrusion manufacturing (PEM), multiphase jet solidification (MJS), precision extrusion deposition (PED), and 3D fiber deposition [31][32][33][34] . FDM technique is the most commonly used nozzle based 3D printing method in which thermoplastic filaments such as poly(lactice acid) (PLA) and acrylonitrile-butadienestyrene (ABS) are melted by heating and extruded on the build plate [35] .…”
Section: Nozzle-based Hydrogel 3d Printing Systemsmentioning
confidence: 99%